2023
DOI: 10.1021/acs.jpcc.2c08378
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Carrier Transfer Dynamics in MoSSe/WSSe Vertical and Lateral Heterostructures

Abstract: Ultrafast charge separation and slower electron−hole recombination in semiconductor materials are essential for photocatalyst and photovoltaic applications. By combining time-dependent density functional theory (TD-DFT) with nonadiabatic molecular dynamics (NAMD), MoSSe and WSSe lateral and vertical heterostructures with type-II band alignments show excellent optical capture capability and effective charge separation properties. The electron and hole transfers in the vertical heterostructure occur in 544 fs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…As depicted in Figure , the hcp-Au 30 and bcc-Au 38 NCs present a broader range of vibrational frequency and higher vibrational intensities than fcc-Au 36 and fcc-Au 44 NCs on the same scale, which can be attributed to the shorter Au I –Au I and Au I –S bonds in the former case (see Table ). It was reported that the coupling between electrons and nuclear vibrations in materials plays a crucial role in determining the photoexcited relaxation pathways and carrier lifetimes, , thus establishing that a picture between kernel packing geometry and excited dynamics is imperative for their application.…”
Section: Resultsmentioning
confidence: 99%
“…As depicted in Figure , the hcp-Au 30 and bcc-Au 38 NCs present a broader range of vibrational frequency and higher vibrational intensities than fcc-Au 36 and fcc-Au 44 NCs on the same scale, which can be attributed to the shorter Au I –Au I and Au I –S bonds in the former case (see Table ). It was reported that the coupling between electrons and nuclear vibrations in materials plays a crucial role in determining the photoexcited relaxation pathways and carrier lifetimes, , thus establishing that a picture between kernel packing geometry and excited dynamics is imperative for their application.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of some achievements, the understanding of the interactions between various factors such as band offset, orbital hybridization, and electron–phonon coupling influenced by the dielectric layer remains unclear with regard to their impact on carrier dynamics. Recently, the time-dependent ab initio nonadiabatic molecular dynamics (NAMD) , method has emerged as a valuable tool for gaining insights into photogenerated carrier dynamics in various structures. With this inspiration, we have chosen MoSTe and h BN heterostructures as examples to explore the impact of the dielectric layer on the photoexcitation dynamics behavior in heterostructures. This study aims to provide essential insights for the effective design of future nanoelectronics and photoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%